ABU ALI IBN SINA AND HIS GREATEST WORK: "THE CANON OF MEDICAL SCIENCE" - Хасанова Гузалия Бахтиёровна; Сейдахматов Сардор Тохир угли; Усаров Лочинбек Фарход угли (Galaxy International Interdisciplinary Research Journal, 2024)
The article discusses the meaning and role of medicine in the life of the great physician Abu Ali ibn Sina, as well as his most significant works on medicine. This article is devoted to the consideration of the main works of Ibn Sina on medicine and the influence of medical science on his life, as well as its role and place in his fate.